The Blind Men and the Elephant: Comparing the Study of International Security Across Journals. (26th May 2020) - Hoagland, Jack; Oakes, Amy; Parajon, Eric; Peterson, Susan
Abstract: We use two major datasets collected by the Teaching, Research, and International Policy (TRIP) Project to map the international security subfield, examining conventional wisdom about the subfield's gender composition, theories, methods, and policy relevance. At first glance, articles in security journals appear similar to security articles, in general, political science and international relations field journals on these variables. On closer inspection, however, we find that much of the standard thinking about international security describes only two security journals, International Security (IS) and Security Studies (SS). First, women author a small percentage of articles in these two journals, with little increase over time, whereas a growing share of articles in other top journals has a female author or coauthor. Second, more articles in IS and SS employ a realist theoretical approach, and these journals have been slower to embrace nonparadigmatic scholarship. Third, in contrast with articles published in the other journal types, only a small percentage of articles in IS and SS use quantitative methods. Finally, these journals are more policy prescriptive than journals representing other parts of the discipline. IS, in particular, publishes more articles containing explicit policy recommendations than any other journal. Our understanding of the international security subfield may reveal only part of the metaphorical elephant explored by the blind men if observers do not consider variation in security-related research across different journals and types of journals.